Gridlock a critical discourse analysis on the Manuel "Mar" Roxas III- Alfred Romualdez dialogue on typhoon Yolanda relief and rescue efforts - Estella, Pauline Gidget (2014)
This multi-method discourse analysis examined the power struggles in a post-Yolanda dialogue between Manuel "Mar" Roxas II, the secretary of the Department of Interior and Local Government, and Alfred Romualdez, mayor of Tacloban, Leyte, Philippines. Through critical discourse analysis as the overarching method (aided by conversation analysis, structuralist narratology, and lexical analysis), the political interests and affiliations of both parties were examined vis-a-vis talk patterns, nature of arguments, and choice of words. In the dialogue, the recurring topics, self-contradicting stances (particularly of Roxas), interruptions in conversation turns, and the protracted length of the talk all pointed to high levels of distrust. The findings of this study are important particularly in the context of post-disaster relief and rescue efforts because they shed light on how functionaries, by using the nuances of language, can possibly delay or even jeopardize negotiation proceedings.
Keywords: Super Typhoon Yolanda, 2013; Rehabilitation